Kontroversi Kepemimpinan Wanita: Perbedaan Pandangan Hadis Bukhari Dan UU Pasal 27 Ayat 1 - Annura Nazwa; Arifin, Tajul (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
In this research, we will explore and explain further the link of Bukhari's hadith regarding women's leadership and the provisions of Article 27 paragraph 1 of the Law on Gender Equality in Leadership Positions. This research was conducted using a multidisciplinary approach that combines textual analysis, historical-critical methods, and legal methods. The findings show that Bukhari's hadith about women's leadership needs to be understood in its socio-historical context and cannot be interpreted from the text alone. On top of that, this research found that the spirit of gender equality in Article 27 paragraph 1 of the law is in line with Islamic rules for creating a fair and beneficial system. Therefore, the reconciliation of religious values and positive legal norms regarding women's leadership can be achieved by considering the comprehensive interpretation of the Bukhari hadith and the contextual application of Law Article 27 paragraph 1. Women's leadership is an important issue that has sparked debate throughout the world, including Indonesia . This debate is rooted in the dialectic between religious values and positive legal norms. In Islamic studies, the placement of certain hadiths in the Sahih Bukhari book is often interpreted as preventing women from occupying leadership positions. On the other hand, Article 27 paragraph 1 of the Law firmly guarantees the right of every citizen to take leadership roles without gender discrimination.